1980
DOI: 10.1177/002242788001700104
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Theories of Deviance and Female Delinquency: an Empirical Test

Abstract: A statewide sample of Iowa teenagers was used to test two hypotheses: (1) The strength of the relationship between the independent variables of traditional theories of criminal deviance and self-reported delinquency would be approximately the same for both males and females, and (2) the differences between the sexes in terms of self-reported delinquency could be accounted for by females' less adverse location in relation to these various independent variables. An attempt was made to operationalize key variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(47 citation statements)
references
References 6 publications
6
40
1
Order By: Relevance
“…Using this measure, these authors found that a coefficient linking gender to crime remained statistically significant but was cut to less than half its original magnitude upon controlling for exposure to delinquent peers. Similar results characterize a number of further studies, thus suggesting that delinquent peer exposure may explain a portion of the gap between male and female crime (e.g., Bell 2009;Jensen 2003;Preston 2006;Simons et al 1980), with only limited research finding evidence that delinquent peer exposure is capable of explaining the entire gap between male and female delinquency (Svensson 2003).…”
Section: Learning Theorysupporting
confidence: 78%
“…Using this measure, these authors found that a coefficient linking gender to crime remained statistically significant but was cut to less than half its original magnitude upon controlling for exposure to delinquent peers. Similar results characterize a number of further studies, thus suggesting that delinquent peer exposure may explain a portion of the gap between male and female crime (e.g., Bell 2009;Jensen 2003;Preston 2006;Simons et al 1980), with only limited research finding evidence that delinquent peer exposure is capable of explaining the entire gap between male and female delinquency (Svensson 2003).…”
Section: Learning Theorysupporting
confidence: 78%
“…Some studies suggest that antisocial behavior is more strongly correlated with deviant peer affiliations in boys (Agnew & Brezina, 1997;Mears, Ploegner, & Warr, 1998;Simons, Miller, & Aigner, 1980), whereas others suggest that the relation between deviant peers and antisocial behavior is stronger in girls (Gomme, 1985;Schulenberg et al, 1999). Given these discrepancies in the literature, it is necessary to consider possible confounding factors that may be influencing outcomes.…”
Section: Department Of Psychology Wayne State Universitymentioning
confidence: 99%
“…Studies relying on general theories and correlates disclose too much similarity between the sexes to be explanatory (Canter 1982;Cernkovich and Giordano 1979;Figueira-McDonough, Barton, and Sarri 1981;Jensen and Eve 1976;Norland et al 1979;Simons, Miller, and Aigner 1980;Smith 1979;Wells and Rankin 1985). Canter (1982), for example, tested the hypothesis that socialization experiences which differ by gender produce stronger family ties for girls; these ties, in turn, inhibit their delinquent involvements.…”
mentioning
confidence: 99%